Bioinformatics and Functional Genomics - Marshall, Christina (United States : Callisto Reference, 2021)
Bioinformatics is a rapidly growing branch of science, which integrates the concepts of biology, engineering, mathematics and computer science in order to develop software tools. These tools are used in analyzing and interpreting biological data. Functional genomics is a sub-field of molecular biology, which uses the tools of bioinformatics to understand the diverse aspects of genes such as regulation of gene expression, DNA sequencing, gene transcription, protein-protein interactions, etc. There has been rapid progress in these fields and their applications are finding their way across multiple industries. This book is compiled in such a manner, that it will provide in-depth information about the theory and practice of bioinformatics and functional genomics. Students, researchers, experts, geneticists, biologists and biological engineers will benefit alike from this book.
Includes index.
Includes bibliographical references.
Keywords: Bioinformatics; Bioengineering; Biochemical genetics; Bioinformatics; Biology -- data processing; Computational biology; Computational biology